Using Reclaimed Asphalt and Polymer Modified Asphalt (PMA) to Maximize Cost Saving over the Pavement Life-Cycle in Qatar - Khnaizer, Jean (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Low performing asphalt mixes along with poor construction practices reduce the pavement serviceability and lead to early failure under repetitive traffic. Government agencies are sometimes urged to implement maintenance and rehabilitation at earlier stages throughout the pavement lifecycle. As an innovative pavement material solution, Polymer Modified Asphalt (PMA) along with an optimized recycled asphalt (RA) content in the recycled hot-mix asphalt (HMA) provide higher performance for the hot asphalt mixes (HMA) with an upfront saving on the cost of material, and a reduced maintenance cost over the lifecycle of pavement. While the mix performance is driven by various factors, RA characteristics and PMA properties contribute to the performance of HMA. In this study, RA and PMA mixes were produced using an existing target Job Mix Formula (JMF) of a dense graded 19.0 mm Nominal Maximum Aggregate Size (NMAS) and Pen 60/70 neat asphalt binder. Five recycled HMA were produced using respectively RA content ranging from 15 to 35%. PMA was added to every mix at a fixed percentage in order to match mixes using PMB PG 76E-10 (extremely heavy traffic with ESALs > 30 million). The Marshall mix design method was used to verify the properties of the recycled HMA. This paper highlights the benefits of using PMA with RA in Qatar as an ultimate solution that provides durability, values, and reduced maintenance cost over the lifecycle of the pavement.